Relationship of Woody Plants to Herbaceous Production in Nigerian Savanna - Sanford, William W.; Usman, Sugei; Obot, Emmanuel O.; Isichei, Augustine O.; Wari, Musa (2014)
Evidence is presented that a light, high tree canopy leads to greater production of grasses in the Nigerian Guinea savanna than either full exposure or dense canopy. Furthermore, some shading provides a microenvironment where such favoured species as the Andropogons replace such undesirable species as Schizachyrium sanguineum and Hyparrhenia species. The role of trees in open rangeland in relation to mineral cycling and soil maintenance is briefly discussed. It is recommended that the common practice of clearing all trees to improve rangeland is stopped and a low density of large trees, preferably legumes, be maintained.